2018
DOI: 10.1096/fj.201800443
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin‐like signaling in ants influences metabolic gene expression and locomotor activity

Abstract: Ants are emerging model systems to study cellular signaling because distinct castes possess different physiologic phenotypes within the same colony. Here we studied the functionality of inotocin signaling, an insect ortholog of mammalian oxytocin (OT), which was recently discovered in ants. In Lasius ants, we determined that specialization within the colony, seasonal factors, and physiologic conditions down-regulated the expression of the OT-like signaling system. Given this natural variation, we interrogated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 68 publications
5
27
0
Order By: Relevance
“…Thus, since global knockdown of inotocin affects diuresis, although the receptor is confined to the CNS and no processes of the inotocin-producing neurons extend outside the CNS, it was suggested that inotocin regulates neurosecretory cells that produce a diuretic hormone [158]. More recent work has shown that knockdown of inotocin in Lasius ants results in increased locomotor activity, selfgrooming and influenced expression of genes involved in metabolism [253]. Fig.…”
Section: Vasopressin-like Peptides (Inotocins)mentioning
confidence: 99%
“…Thus, since global knockdown of inotocin affects diuresis, although the receptor is confined to the CNS and no processes of the inotocin-producing neurons extend outside the CNS, it was suggested that inotocin regulates neurosecretory cells that produce a diuretic hormone [158]. More recent work has shown that knockdown of inotocin in Lasius ants results in increased locomotor activity, selfgrooming and influenced expression of genes involved in metabolism [253]. Fig.…”
Section: Vasopressin-like Peptides (Inotocins)mentioning
confidence: 99%
“…Furthermore, behavioral analysis of ants in which inotocin precursor gene expression had been knocked-down revealed increased locomotor activity and increased self-grooming in the brood chamber. Based on these findings, the authors concluded that inotocin signaling is important for regulation of energy status in association with locomotion and appetite in Lasius neglectus (68).…”
Section: Arthropodamentioning
confidence: 97%
“…Collectively, these findings led the authors to propose that when Camponotus worker ants start foraging, where there is an increased risk of dessication, inotocin signaling acts to stimulate synthesis of protective CHCs. In this context it is interesting that knockdown of inotocin expression in L. neglectus causes increased locomotor activity (68). Thus, inotocin signaling may act at a physiological level to stimulate synthesis of protective CHCs (Camponotus) and at a behavioral level to inhibit locomotor activity (L. neglectus) as integrated adaptive mechanisms to minimize dessication.…”
Section: Arthropodamentioning
confidence: 99%
See 2 more Smart Citations